PENGARUH KOMPENSASI FINANSIAL, KOMUNIKASI DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN - Yasa, I Ketut Manik Swardika; Wibawa, I Made Artha (E-Jurnal Manajemen, 2015)
Morale is the willingness and sincerity one has done his job well and achieve maximum performance, which stimulates a person to work and creativity in the work. This study aimed to determine the effect of financial compensation, communication and physical work environment on employee morale. This research was conducted at PT. Sang Tunas Sejahtera. The sample of this study all employees totaling 52 people, with the saturated sample method. Data collected through observation, interviews and questionnaires. The analysisitechnique usediis multipleilinear regression analysis. The results of the analysis found that financial compensation, communication and physical work environment affects simultaneously and partially on employee morale. The company should consider the suitability of incentives with the performance of employees, pay attention to communication and attention to the work environment of employees.
Keywords: Financial compensation, Communication, Physical Work Environment and Morale